2017
DOI: 10.4084/mjhid.2017.039
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Aetiology of Bacteremia in Febrile Children With Sickle Cell Disease at a Nigerian Tertiary Hospital

Abstract: Background & ObjectivesAs a result of immune defects in Sickle cell disease (SCD), affected individuals are prone to infection from encapsulated bacterial pathogens like Streptococcus Pneumoniae. Studies on the etiological agents of bacteremia in children with SCD in Nigeria are few and have revealed a spectrum of organisms that is different from those recorded in other parts of the world.Aim and ObjectivesThe objectives of this study were to determine the prevalence of bacteremia, etiological agents and antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
(41 reference statements)
1
18
1
Order By: Relevance
“…The prevalence of bacteraemia was 13.8% in febrile SCD positive children attending a tertiary hospital in Ibadan, South West-Nigeria. 17 However, in both studies, Gram-negative bacilli were predominantly the cause of bacteraemia, which is similar to a study conducted in Israel, 18 where an emerging presence of Gram-negative isolates in post-splenectomy patients, including SCD subjects, was reported. The significant difference in prevalence of bacteraemia, especially of Salmonella species , Streptococcus pneumoniae and Klebsiella pneumoniae among febrile SCD positive children recorded in Ibadan 17 and this study could be due to differences in traditional/religion beliefs and cultural practices of the two populations toward SCD, vaccination and general acceptability of hospital at the onset of illness.…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence of bacteraemia was 13.8% in febrile SCD positive children attending a tertiary hospital in Ibadan, South West-Nigeria. 17 However, in both studies, Gram-negative bacilli were predominantly the cause of bacteraemia, which is similar to a study conducted in Israel, 18 where an emerging presence of Gram-negative isolates in post-splenectomy patients, including SCD subjects, was reported. The significant difference in prevalence of bacteraemia, especially of Salmonella species , Streptococcus pneumoniae and Klebsiella pneumoniae among febrile SCD positive children recorded in Ibadan 17 and this study could be due to differences in traditional/religion beliefs and cultural practices of the two populations toward SCD, vaccination and general acceptability of hospital at the onset of illness.…”
Section: Discussionsupporting
confidence: 81%
“…In Africa, bacteremia was found in 14% to 32% in children with SCD. 5154 This was much higher than the incidence observed in high-income countries 55,56. Reversely, to what is observed in Western countries, pneumococcal infection in Africa does not contribute significantly to the morbidity and mortality of children with SCD because of the involvement of other infections, rending preventive measures inappropriate 57.…”
Section: Infections With Specific Pathogens In Scdmentioning
confidence: 85%
“…Reversely, to what is observed in Western countries, pneumococcal infection in Africa does not contribute significantly to the morbidity and mortality of children with SCD because of the involvement of other infections, rending preventive measures inappropriate 57. Gram-negative bacteremia constitute more than 60% of all isolates, while the predominant isolates were Klebsiella pneumonia (25%), Staphylococcus aureus (25%), and Salmonella species 51,52,54,5862. One given explanation for these discrepancies in terms of patterns of bacterial isolates was the unregulated use of antibiotics (mainly penicillins or penicillin derivatives) before hospital admission in some African countries, which could affect the results of bacterial cultures 51,63.…”
Section: Infections With Specific Pathogens In Scdmentioning
confidence: 86%
“…Most reports included information on penicillin prophylaxis, although adherence was not formally assessed, and all studies reported introduction of a PCV programme except the study from Nigeria, where vaccination uptake was reported to be poor (Brown et al , ). In studies that reported vaccination status, the proportion of IPD cases that were vaccinated with PCV varied significantly from 0% to 80% (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…pre-or post-PCV era); this study was excluded. The remaining 16 studies were included in the final analysis (Halasa et al, 2007;Adamkiewicz et al, 2008;Rogovik et al, 2010;McCavit et al, 2011;Narang et al, 2012;Baskin et al, 2013;Chang et al, 2013;Ellison et al, 2013;Patel et al, 2013;Payne et al, 2013;Shihabuddin & Scarfi, 2014;Soothill et al, 2016;Brown et al, 2017;Navalkele et al, 2017;Martin et al, 2018;Oligbu et al, 2018). We found large variations in study methodology and quality.…”
Section: Study Characteristicsmentioning
confidence: 99%